2011
DOI: 10.1093/infdis/jir444
|View full text |Cite
|
Sign up to set email alerts
|

Measles Outbreak in Venezuela: A New Challenge to Postelimination Surveillance and Control?

Abstract: The circulation of wild measles virus was interrupted in Venezuela in February 2007 after the catch-up vaccination (1994) and monitoring (1998) and in response to the measles outbreak in 2001. Traditionally, the routine coverage with measles-mumps-rubella vaccine does not exceed 85%. In February 2006, a measles outbreak started by importation in the State Miranda; this extended to 7 states and lasted 50 weeks with an intermediate period of 17 weeks without reported cases. New cases were reported in the States … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 1 publication
0
14
0
2
Order By: Relevance
“…In Venezuela, circulation of wild measles was interrupted in February 2007 after a mass vaccination campaign that followed outbreaks in 2001 and 2006 ( 15 ). However, since 2017, measles has reemerged in Venezuela, particularly within vulnerable indigenous populations, and has subsequently reached neighboring countries (Figure 1, panel A) ( 16 ).…”
Section: Measlesmentioning
confidence: 99%
“…In Venezuela, circulation of wild measles was interrupted in February 2007 after a mass vaccination campaign that followed outbreaks in 2001 and 2006 ( 15 ). However, since 2017, measles has reemerged in Venezuela, particularly within vulnerable indigenous populations, and has subsequently reached neighboring countries (Figure 1, panel A) ( 16 ).…”
Section: Measlesmentioning
confidence: 99%
“…A study evaluating the measles clinical case definition in New York City reported the negative predictive value of the case definition at 98% ( 36 ). Similarly, Sarmiento et al ( 37 ) reported a negative predictive value of 86% of the clinical case definitions in their study in Venezuela. Furthermore, a review of four studies reported that the sensitivity of the clinical case definition was high (76%–88%).…”
Section: Discussionmentioning
confidence: 70%
“…These data indicate that the epidemiology of measles is changing from widespread prevalence to more limited, focal outbreaks. The experience from WHO Region of the Americas showed that, as the region progressed towards elimination, measles epidemics were usually concentrated in areas with poor implementation of the vaccination strategy, such as the measles outbreak that occurred in Sao Paulo in Brazil in 1997, and the measles outbreak in Venezuela . It is important to note that nosocomial infections are now important risk factors for measles epidemics in China .…”
Section: Discussionmentioning
confidence: 99%